General English for first-year students. Term 2 электронный курс - Кудряшова, А. В. лингвист старший преподаватель Томского политехнического университета 1979- (TPU Moodle, 2015)
The course General English for first-year students - Term 2 is developed for learning English for General Purposes by the first year students of the Institute of Cybernetics. The course is intended for developing listening, reading, writing and speaking skills, revising grammar material and increasing vocabulary on the topics concerned.